Evaluation of the Ribosomal Protein S1 Gene (rpsA) as a Novel Biomarker for Mycobacterium Species Identification - Duan, Hongfei (Biomed Res Int, 2015)
Objectives. To evaluate the resolution and reliability of the rpsA gene, encoding ribosomal protein S1, as a novel biomarker for mycobacteria species identification. Methods. A segment of the rpsA gene (565 bp) was amplified by PCR from 42 mycobacterial reference strains, 172 nontuberculosis mycobacteria clinical isolates, and 16 M. tuberculosis complex clinical isolates. The PCR products were sequenced and aligned by using the multiple alignment algorithm in the MegAlign package (DNASTAR) and the MEGA program. A phylogenetic tree was constructed by the neighbor-joining method. Results. Comparative sequence analysis of the rpsA gene provided the basis for species differentiation within the genus Mycobacterium. Slow- and rapid-growing groups of mycobacteria were clearly separated, and each mycobacterial species was differentiated as a distinct entity in the phylogenetic tree. The sequences discrepancy was obvious between M. kansasii and M. gastri, M. chelonae and M. abscessus, M. avium and M. intracellulare, and M. szulgai and M. malmoense, which cannot be achieved by 16S ribosomal DNA (rDNA) homologue genes comparison. 183 of the 188 (97.3%) clinical isolates, consisting of 8 mycobacterial species, were identified correctly by rpsA gene blast. Conclusions. Our study indicates that rpsA sequencing can be used effectively for mycobacteria species identification as a supplement to 16S rDNA sequence analysis.